Psychopathic Deviate Tendency and Psychopathology Relationships in an Iranian Adolescents and Youth Sample: Gender Differences and Predictors (European Journal of Mental Health, 2010)
The present study examines psychopathic deviate tendency and psychopathology relationships and the possible gender differences in them in an Iranian adolescents and youth sample. The sample included 106 adolescents (55 females and 51 males) and 94 youth (45 females and 49 males) that were randomly selected from Eghlid city, Fars province, Iran. We speculated a possible linkage between psychopathology and psychopathic deviate tendency among adolescents and youth on the basis of developmental psychopathology and related literature. A demographic questionnaire, the Minnesota Multiphasic Personality Inventory–2, scale–4, and the Symptom Check List 90 Revised were used in this study. Analysis indicated that psychopathic deviate tendency and psychopathology indices were linearly related in adolescents and youth. There are significant positive correlation coefficients between the psychopathic deviate tendency and psychopathology including somatisation, obsessive-compulsive disorder, anxiety, interpersonal sensitivity, aggression, phobia, paranoid ideation, psychosis, atypical factors and SCL–90–R. However, significant correlations between psychopathic deviate tendency, somatisation and phobia are elements that give a new insight into this research. A multivariate analysis of variance conducted by gender, age group and gender-age group interaction as independents and the psychopathic deviate tendency and psychopathology indices as dependents variables that reject their significant effects in both dependents’ variables. Finally, the multiple regressions indicated that paranoid ideations, somatisation and aggression, somatisation, depression, and somatisation predict psychopathic deviate tendency in females, males, adolescence, youth, and total sample respectively.